2017
DOI: 10.1039/c7ra09605d
|View full text |Cite
|
Sign up to set email alerts
|

Rheological reversibility and long-term stability of repulsive and attractive nanoemulsion gels

Abstract: In this research, the stability of sodium dodecyl sulfate (SDS)-stabilized canola oil nanoemulsion gels was investigated as a function of repeated rotational shear, oscillatory strain and storage time. Nanoemulsion gels, termed nanogels, were formed from oil-in-water nanoemulsions, prepared with various concentrations of SDS to get a range of droplet sizes, interdroplet interactions, and gel strengths.Repulsive nanogels were formed with 0.5, 1 and 2 times the critical micelle concentration (CMC), while attract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…3C) indicate a network of packed polymeric chains and the correlation with tan(δ) confirmed for both hydrogels liquid-like behaviors rather than a solid-like nature. Moreover, the intersection of G′ and G″ occurs at lower values in chem-HG than in phys-HG (at shear stress τ = 131 Pa and τ = 345 Pa) indicating more stiffness in the chemical network according to the presence of both amide and electrostatic cross-linking that probably create preferential break-lines compared to the physical gel under the same strain [59]. One hydrogel distinctive feature is the ability to retain high amount of water.…”
Section: Hydrogel Physical Propertiesmentioning
confidence: 99%
“…3C) indicate a network of packed polymeric chains and the correlation with tan(δ) confirmed for both hydrogels liquid-like behaviors rather than a solid-like nature. Moreover, the intersection of G′ and G″ occurs at lower values in chem-HG than in phys-HG (at shear stress τ = 131 Pa and τ = 345 Pa) indicating more stiffness in the chemical network according to the presence of both amide and electrostatic cross-linking that probably create preferential break-lines compared to the physical gel under the same strain [59]. One hydrogel distinctive feature is the ability to retain high amount of water.…”
Section: Hydrogel Physical Propertiesmentioning
confidence: 99%
“…It was claimed that the floc size would increase by raising the polymer’s charge density and molecular weight 39 . In addition, these results indicated that increasing the KLDs dosage enhanced the floc growth as well 46 .
Figure 5The floc size distribution of kaolin particles in the presence and absence of KLD at dosage of 8 and 32 mg/g, conducted under the conditions of pH 7, 25 °C and 0.4 g/L of kaolin concentration.
…”
Section: Resultsmentioning
confidence: 84%
“…A significant decrease in G’ could be observed as a function of time for SDS‐stabilized canola oil NE gels. The loss of gel strength in the canola oil NE gels was explained by the change in interfacial charge cloud due to the generation of surface active lipid oxidation products . The canola oil was found to be significantly oxidized after 90‐day storage.…”
Section: Long‐term Stability Of Nanoemulsion Gelsmentioning
confidence: 97%
“…Most importantly, the gel strength did not change as a function of time. While SDS is known to induce lipid oxidation by attracting pro‐oxidant metal ions, milk proteins, such as sodium caseinate, are effective antioxidant due to the formation of a thick interfacial barrier, the presence of antioxidative amino acids and the ability to scavenge metal ions . We propose that the oxidative protection of the oil by SC could be the main reason behind the excellent stability of NE gel upon long‐term storage.…”
Section: Long‐term Stability Of Nanoemulsion Gelsmentioning
confidence: 97%